Biofunctional porous anodized titanium implants for enhanced bone regeneration. Issue 10 (21st November 2013) - Shim, In Kyong; Chung, Hye Jin; Jung, Mi Ra; Nam, Seung Yeon; Lee, Su Young; Lee, Hyukjin; Heo, Seong Joo; Lee, Seung Jin
Abstract Efficient osseointegration is a key factor in dental implants to reduce the total time‐course of therapy. Titanium implants with anodized surface gained much interest for their enhanced osseointegration. Anodized implant combined with bioactive drugs is an ideal candidate for enhance bone regeneration. Previously delivery of drugs from the metal implants has been attempted by utilizing a polymeric dip‐coating method. However, the entire surface coating with polymer can diminish the advantageous surface roughness of anodized implants and cause contact inhibition between bone and implant surface. In this study, fibroblast growth factor‐2 (FGF‐2) loaded poly(lactide‐co‐glycolide) nanoparticles were partially coated on anodized Ti discs by an electrospray deposition. Nanoparticle coated anodized discs maintained their native porous structure and provided a sustained release of FGF‐2 for more than 2 weeks with 40% initial burst. In vitro study confirmed the influence of polymeric nanoparticles and the release of growth factors from the Ti disc. Nanoparticle‐coated groups significantly enhanced cell spreading and differentiation. For in vivo evaluation, the anodized titanium implants were applied to rabbit tibia model. The osseointegration was estimated by bone to implant contact of best three consecutive threads at the border of the implant. The mean osteointegration value of FGF‐2 releasing implant groups (70.1%) was significantly higher than that of untreated implants (47.1%). We believe that the electrospray deposition technique is a particularly attractive approach for the coating of medical devices with porous surface to maintain their surface topography while allowing a sustained delivery of growth factors for bone regeneration. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3639–3648, 2014.